Nomenclatural notes on Ferula tunshanica (= F. licentiana var. tunshanica) (Apiaceae) - Li, J. P.; Peng, X. M.; Yu, W. B. (Phytotaxa, 2010)
The holotype of Ferula tunshanica S.W.Su is the flowering herbarium specimen Wen-Zhe Fang, Ping-Ping Ling, et al. 74020 (NAS), and not 7402 as reported in the original description. Subsequent authors have treated this taxon at varietal rank within F. licentiana Hand.-Mazz., but confusion exists as to the correct author, date and place of publication for var. tunshanica. Our research shows that var. tunshanica was validly published in 1992 by K. M. Shen in Flora Reipublicae Popularis Sinicae, and so should be cited as F. licentiana var. tunshanica (S.W. Su) R.H. Shan & Q.X. Liu ex K.M. Shen.